2006
DOI: 10.7326/0003-4819-145-5-200609050-00136
|View full text |Cite
|
Sign up to set email alerts
|

National Institutes of Health State-of-the-Science Conference Statement: Multivitamin/Mineral Supplements and Chronic Disease Prevention

Abstract: NIH consensus and state-of-the-science statements are prepared by independent panels of health professionals and public representatives on the basis of (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 11 publications
0
26
1
Order By: Relevance
“…In this analysis, we followed the National Institutes of Health definition, which defined MVM as dietary supplements comprising >3 vitamin and mineral ingredients. 10 Supplements containing herbs, hormones, or drugs were excluded from the analysis. We included studies that assessed MVM supplement use by a questionnaire or in a follow-up office visit.…”
Section: Definition Of Mvm Use and Cardiovascular Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, we followed the National Institutes of Health definition, which defined MVM as dietary supplements comprising >3 vitamin and mineral ingredients. 10 Supplements containing herbs, hormones, or drugs were excluded from the analysis. We included studies that assessed MVM supplement use by a questionnaire or in a follow-up office visit.…”
Section: Definition Of Mvm Use and Cardiovascular Outcomementioning
confidence: 99%
“…7,9 Based on the weak and controversial benefit of MVM supplements, the US Preventive Services Task Force and the National Institutes of Health recommend against the routine use of MVM supplements for the purpose of chronic disease prevention, including CVD. 10,11 However, the prevalence of MVM supplementation in the general population remains high; for example, the National Health and Nutrition Examination Survey 2011 to 2012 data showed ≈30% of the population in the United States as using MVM supplements. 1,12,13 According to projections from 1 financial report, the global nutritional supplement industry is expected to reach $278 billion USD by 2024.…”
mentioning
confidence: 99%
“…In the United States the use of dietary supplements has increased substantially over the past several decades 1,2,3 , reaching approximately one-half of adults in 2000 and annual sales of over $20 billion. 1,3 We reported that 66% of women participating in the Iowa Women's Health Study (IWHS) used at least one dietary supplement daily in 1986 at average age 62 years, while in 2004, the proportion increased to 85%.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 We reported that 66% of women participating in the Iowa Women's Health Study (IWHS) used at least one dietary supplement daily in 1986 at average age 62 years, while in 2004, the proportion increased to 85%. 2 Moreover, 27% of women reported using four or more supplemental products in 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation